2014
DOI: 10.1038/cddis.2014.482
|View full text |Cite
|
Sign up to set email alerts
|

SHMT1 knockdown induces apoptosis in lung cancer cells by causing uracil misincorporation

Abstract: Reprogramming of cellular metabolism towards de novo serine production fuels the growth of cancer cells, providing essential precursors such as amino acids and nucleotides and controlling the antioxidant and methylation capacities of the cell. The enzyme serine hydroxymethyltransferase (SHMT) has a key role in this metabolic shift, and directs serine carbons to one-carbon units metabolism and thymidilate synthesis. While the mitochondrial isoform of SHMT (SHMT2) has recently been identified as an important pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 31 publications
7
103
1
1
Order By: Relevance
“…Our functional analyses now suggest a direct stimulating effect of overexpression of SHMT1 on tumor cell proliferation. This is in accordance with the increased expression of SHMT1 that was recently found in lung cancer [Paone et al, 2014]. However, the inhibitory effect of SHMT1 overexpression on migration and invasion of the osteosarcoma cells that we noted was not expected and remains to be clarified.…”
Section: Discussionsupporting
confidence: 75%
“…Our functional analyses now suggest a direct stimulating effect of overexpression of SHMT1 on tumor cell proliferation. This is in accordance with the increased expression of SHMT1 that was recently found in lung cancer [Paone et al, 2014]. However, the inhibitory effect of SHMT1 overexpression on migration and invasion of the osteosarcoma cells that we noted was not expected and remains to be clarified.…”
Section: Discussionsupporting
confidence: 75%
“…Mammalian Shmt1 also serves as a scaffold protein that facilitates the interaction with DHFR and thymidylate synthase at the nuclear lamina (77). Remarkably, inactivation of Shmt1 in mice (78,79) or its down-regulation in human lung cells (80) results in increased uracil incorporation into DNA as result of impaired de novo dTMP biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this hypothesis, quantitative metabolic flux analysis done in mammalian cells revealed that the C1 cycle, through oxidation of 5,10-CH 2 -THF, contributes to the production ∼40% of NADPH (82), a central cofactor in redox homeostasis. Alternatively, loss of Shm2 in S. cerevisiae, similar to inactivation of mammalian Shmt1 (78,80), might cause uracil accumulation and increased mutagenesis. However, our analysis in shm2Δ mutants did not reveal major differences in NTP/dNTP pools or signs of DDR activation.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction catalyzed by SHMT1 is an important source of glycine [14,15] and hypoglycinemia was shown to contribute to occurrence of vascular calcification and elevated cardiovascular risk in diabetes and CKD [47]. Furthermore, direct targets of SHMT1-mediated methylation [18][19][20][21] may be involved in osteoinductive signaling in VSMCs. Conversely, SHMT1 may mediate anti-calcific effects of folate-dependent pathways to protect against vascular calcification [48].…”
Section: Discussionmentioning
confidence: 99%
“…One carbon transfer is a key component in amino acid and nucleotide synthesis as well as methylation of proteins, DNA and RNA [18,19] and, thus, participating in the regulation of cell function, proliferation and growth [18,20]. SHMT1 has been associated with apoptotic pathways [21]. SHMT1 differs in targets and effects from the mitochondrial isoform SHMT2 [14,15,18].…”
Section: Introductionmentioning
confidence: 99%